NEGOTIATING POWER AND COLLECTIVE ADVOCACY STRATEGIES AMONG JAKARTA’S HOME-BASED WORKERS IN A PUTTING-OUT SYSTEM - Pamungkas, Reza Tri; Arif, Akbarudin; Saptaningtyas, Haryani (Journal of Social Politics and Governance (JSPG), 2025)
This study examines the collective advocacy strategies of the Jakarta Home-Based Workers Network (JPRJ) in addressing structural inequalities affecting women home-based workers under the putting-out system. Although collective organizing can generate counter-power at the community level—manifested as power within, power with, and power to—the movement continues to face structural barriers. These obstacles emerge from state strategies that dilute labor demands through tokenistic participation and by reframing home-based workers as micro-entrepreneurs rather than as legal subjects entitled to labor rights. Using John Gaventa’s Power Cube and Jo Rowlands’s empowerment framework, the study analyzes how hidden and invisible power sustain exploitative labor relations. Through a qualitative case study in North Jakarta, the findings show that JPRJ cultivates critical consciousness, strategic alliances, and actions that strengthen collective advocacy. These efforts include a judicial review of the Manpower Act and the creation of alternative community spaces such as the Pos UKK and worker cooperatives. The study concludes that the success of home-based worker advocacy at the macro level depends on collective solidarity and on dismantling state-led identity reframing that obscures workers’ legal status. Policy recommendations include ratifying ILO Convention No.177, establishing national regulations recognizing home-based workers, and integrating their data into official labor statistics.